Frequency Response and Power Dissipation of RC Coupled CE Amplifier by Using Series and Parallel Network of Like Transistors. Issue 1 (23rd February 2023) - Tiwari, Satyendra Nath; Khadarabad, Ghouse Mohiuddin; Pandey, Anoop Kumar; Dwivedi, Apoorva; Pandey, Shri Prakash; Singh, Vijay
Abstract: The RC‐coupled small‐signal amplifier is a widely used circuit that serves as a basic building block in electronic circuits. The study of amplifier circuits with various component modifications may yield important results that can be utilized to improve circuit designs based on application needs. Using the Pspice 9.5.2 simulation tool, a study of a BJT‐based CE amplifier is carried out to determine the dependence of frequency response, bandwidth, maximum voltage gain, power dissipation, input impedance, and other parameters while using a network of BJTs coupled in parallel and in series from Q1 to Qn.